The reproduction of mothering: psychoanalysis and the sociology of gender - Chodorow, Nancy (University of California Press, 1978)
When this best-seller was published, it put the mother-daughter relationship and female psychology on the map. The Reproduction of Mothering was chosen by Contemporary Sociology as one of the ten most influential books of the past twenty-five years. With a new preface by the author, this updated edition is testament to the formative effect that Nancy Chodorow's work continues to exert on psychoanalysis, social science, and the humanities.
Keywords: 1900-1999; amériques; cours; cycles supérieurs; discipline; fem1000; fem9000; figure de la mère; genre; identités LGBTQIA2+; maternité; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; états-unis

Maternité esclave - Collectif les Chimères (Union générale d'éditions, 1975)
Le titre sonne comme une condamnation. Le texte, toujours vif, souvent violent, parfois plein d'humour, est un texte de combat. Des féministes, qui se sont réunies pour écrire ensemble ce qu'elles pensent des conditions de la maternité, poursuivent ici un combat qu'elles ont déclenché en avril 1971 avec le manifeste des 343.
Keywords: 1900-1999; 1970-1979; approches et analyses; corps; cours; cycles supérieurs; europe; fem9000; france; féminisme matérialiste; maternité; périodes historiques; régions géographiques; thématiques